Barriers to Participating in a Payment for Ecosystem Services Project in Githambara Micro Catchment, Upper-Tana, Kenya - Wangui, Elizabeth Edna; Nijbroek, Ravic P. (International Center for Tropical Agriculture, 2018)
International Non-Governmental Organizations have popularized payment for ecosystem services (PES) because of their potential to simultaneously achieve rural development and ecological conservation goals (GEF Secretariat 2014). Despite their rapid diffusion, there is insufficient assessment of their potential implications for social and economic stratification (Redford and Adams 2009). Indeed, there is growing evidence that PES may reproduce or even exacerbate existing inequalities in social development and resource access (Kosoyand Corbera2010, Porras 2010). However, the gender dimensions of PES impacts has been the focus of little scholarship, despite concerns about women’s exclusion from participating (e.g., Kariukiand Birner2016) or their inclusion in ways that reduce their decision-making power within the household (e.g., Schwartz 2017). This research uses a feminist political ecology lens to add to this small but growing body of work through an examination of how the PES program implementation influences gendered equity in access and outcomes of the associated sustainable land management (SLM) practices.